THE LEGAL PARADIGM OF THE RESTORATION OF UKRAINE: PROBLEMS AND PERSPECTIVES - Sopilko, Iryna; Iurynets, Julia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: summarizing the results of the 14th International Scientific and Practical Conference "The Legal Paradigm of the Restoration of Ukraine: Problems and Prospects", and developing proposals for the intensification of research aimed at solving specific problems of the restoration of Ukraine, which require an urgent solution. Research methods: to achieve the goal of the research, general and special methods were used, in particular the functional-legal, structural-systemic, generalization and other methods. Results: the generalized tasks outlined by the participants of the conference, which (tasks) appeared on the agenda of Ukrainian legal science in the conditions of the restoration of Ukraine, in particular, consist in the scientific substantiation of issues related to legal values as determinants of the development strategy of Ukraine in the conditions of European integration; innovative modernization of public-legal relations in Ukraine: focus on strategy during the war and post-war recovery; modern trends in the development of criminal and legal science and law enforcement activities; the vision of national private law in the post-war period; trends in the development of economic, air and environmental law through the prism of the world experience of post-war reconstruction of the country and national characteristics. Discussion: on March 1, 2022, the European Parliament at an extraordinary meeting considered Ukraine’s submission and recommended granting it the status of a candidate for EU accession, which imposes obligations on the country to meet the membership criteria. It was established that in order to ensure Ukraine’s compliance with EU legal values, it is necessary to implement a number of measures, in particular to adopt and bring national legislation into line with European standards, to create an effective system of justice and law enforcement agencies, to ensure compliance with human rights and fundamental freedoms; taking into account the complexity of the interrelationships between military conflict and legal values, there is a growing need to preserve universal human values in law, especially regarding the protection and observance of human rights and freedoms, actualization of the issue of responsibility for war crimes, compensation for damage caused, payment of reparations.